2016
DOI: 10.3389/fphys.2016.00535
|View full text |Cite
|
Sign up to set email alerts
|

Larval Exposure to Chlorpyrifos Affects Nutritional Physiology and Induces Genotoxicity in Silkworm Philosamia ricini (Lepidoptera: Saturniidae)

Abstract: Chlorpyrifos is a most widely used organophosphate insecticide because of its cost effectiveness and degradable nature. However, this pesticide enters and contaminates the environment either by direct application, spray drifts or crop run off and shows adverse effect on the non-targeted organisms. Philosamia ricini (eri silkworm), one of the most exploited, domesticated and commercialized non mulberry silkworm is known for mass production of eri silk. The silkworm larvae get exposed to pesticide residues on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
0
8
1
Order By: Relevance
“…Morimoto et al ( 2004) using an exposure through artificial diet, found that the lepidopteran Spodoptera litura had an LC₅₀ of 12.8 mg/L when exposed to another organophosphate, acephate. Greater toxicity of chlorpyrifos than that found here was reported by Kalita et al (2016) who found an LC₅₀ of 3.35 mg/L at 96 h in the silkworm (Philosamia ricin) indicating the potential for significant variation in species sensitivity among lepidopterans for this insecticide.…”
Section: Tablecontrasting
confidence: 48%
“…Morimoto et al ( 2004) using an exposure through artificial diet, found that the lepidopteran Spodoptera litura had an LC₅₀ of 12.8 mg/L when exposed to another organophosphate, acephate. Greater toxicity of chlorpyrifos than that found here was reported by Kalita et al (2016) who found an LC₅₀ of 3.35 mg/L at 96 h in the silkworm (Philosamia ricin) indicating the potential for significant variation in species sensitivity among lepidopterans for this insecticide.…”
Section: Tablecontrasting
confidence: 48%
“…and found dose-dependent comet formation at 24-h and 48-h exposure, which decreased with extended exposure times up to 96 h owing to DNA damage repair. Numerous studies have tested commercial formulations of chlorpyrifos on rats (Ezzi et al, 2016), mice (Chauhan et al, 2016), silkworms (Kalita et al, 2016) and fish (Ismail et al, 2014;Vera-Candioti et al, 2014), reporting the positive genotoxic effects. Even the occupational exposure to mixtures of insecticides including chlorpyrifos formulations has been associated with observed MN induction (Omari, 2011;Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Organophosphate (OP) pesticides are used worldwide to control parasites in agriculture, industry, and households ( Terry, 2012 ; Kalita et al, 2016 ). The OP trichlorfon, is used to control various parasitic infestations in human medicine, agriculture, and aquaculture industries ( WHO, 1992 ).…”
Section: Introductionmentioning
confidence: 99%